Waqifiyya in Shi'a Hadith Thought and the Value of Narrations Coming from Them - Demir, Abdulalim (Anadolu Ilahiyat Akademisi, 2024)
Shi'a has divided into many sects due to various reasons throughout the historical process. One of the sects formed as a result of these divisions is Waqifiyya. The word Waqifi has been used in different contexts in many sects, In Shi'a terminology, for those who do not accept the death of Imam Musa al-Kazim when he is used in absolute terms, reject the imamate of his son 'Ali al-Rida who was appointed after him, adopt the idea that al-Kazim will return as the Mahdi and continue their beliefs on his imamate and jurisprudence. is used. Although materiality played an important role in the emergence of Waqifiyya, it is seen that other reasons also had an impact. The main factor that makes Waqifiyya important in terms of Shi'a hadith science is that the situation of the narrators who have this idea in terms of justice and control and whether the issue of whether they can bring evidence from the narrations conveyed through them remains current in the history of Shi'a hadith. Therefore, knowing Waqifiyya in detail will help to understand the internal criticism mechanism in the sect and the methods of approaching the sects that Shi'a sees as other. Although many studies have been conducted focusing on other sects of Shia, no independent study has been conducted on Waqifiyya.Our study aims to contribute to this deficiency seen in the literature. In the article, what is the value of Waqifiyya and the narrations coming from them in Shia hadith thought? The answer to the question is sought. In order to better understand the issue, the study will examine the subject from a descriptive and analytical perspective, paying utmost attention to the principle of idea-event connection. For this purpose, documentation analysis method, one of the qualitative research methods, will be used. In the final analysis, although Shi'a accuses the Waqifis s of lying, atheism, infidelity and distorting narrations, they attach value to the narrations coming from their sect and use their narrations wherever they need within certain conditions. It is possible to explain this with the dominance of those who adopt the Wakifi view in the sect, and the narrations coming through them are widely included in the hadith and rijal books and have become established in the sect.
Keywords: Hadith; Shi'a Imamiyah; Waqifiyya; Musa al-Kazim; 'Ali al-Rida